Cervical cytology screening in La Libertad Region, 2010 - Albújar-Baca, Pedro (2013)
Objectives: To measure the conventional cervical cytology coverage screening in the Region La Libertad, to establish the frequency of confirmatory biopsy in patients with high grade cytology and the fulfillment of the cervical screening guidelines. Material and method: The 2010 cervical cytology reports of the Laboratories were compiled. The frequency of confirmatory biopsy, one year after the high grade cytology report, was recorded. The heads of the Pathology Laboratories were interviewed about the accomplishments of the screening guidelines. Results: The regional screening coverage was 9,0 %. Only 36,3 % of patients with high grade cytology had confirmatory biopsy. The cytology screening guidelines were not fulfilled. Conclusión: The cervical screening Program for cervical cancer and precursors require fundamental changes to achieve the control of the disease.